Efficient and Scaleable Web-Based Path Rendering - Unlocking the Potential of Compute Shaders on the Web - Karmetun, Oliver (My University, 2024)
With the rise of simulation and digital twin technology within the industry there has been an increased interest in taking advantage of web-based rendering, because of its user accessibility and device compatibility. However, this introduces challenges such as limitations on data transfer, data storage and limited API capabilities compared to classic rendering solutions. This is especially problematic for massive simulations such as those used within the autonomous vehicle industry. This thesis aim to demonstrate how technologies recently introduced to a web context, such as compute shaders, can be used to accelerate the common problem of path rendering or stroking, which is the rendering of visible curves on the screen. Our method is general and allows for rendering dynamic paths with dynamic levels of detail. Performance is comparable to other high performance solutions.
Keywords: Computer science; computer graphics; vector graphics; stroking; web; rendering